Organochlorine levels in cetaceans from South Africa: A review - Cockcroft, V.G. (J. Cetacean Res. Manage., 1999)
Publications on levels of organochlorines in cetaceans from South Africa are reviewed. Organochlorine contamination in cetaceans off South Africa is similar to those in Australian waters, but generally low compared to the Northern Hemisphere. An exception is the coastal dolphins inhabiting the South African east coast waters. In these animals levels are similar to Northern Hemisphere coastal cetaceans. Levels are generally higher in coastal dolphins, compared to dolphins living in deeper waters. It is suggested that these differences are directly related to the levels of industrialisation and cultivation of the surrounding area. Too few samples of either baleen whales or toothed whales are available to investigate the differences in Organochlorine levels between these two groups. Similarly, even for species with the highest sample sizes — common and bottlenose dolphins — the data are insufficient to investigate trends in contaminant levels.